2001
DOI: 10.1046/j.1365-2648.2001.01792.x
|View full text |Cite
|
Sign up to set email alerts
|

The primary and secondary care interface: the educational needs of nursing staff for the provision of seamless care

Abstract: R . ( 2 0 0 1 ) Journal of Advanced Nursing 34(5), 629±638 The primary and secondary care interface: the educational needs of nursing staff for the provision of seamless care Aim. To identify nurses' perceived de®cits in the knowledge and skills required to provide effective seamless care, so that appropriate training could be provided. Background. A clear understanding of nursing staff roles, skills and resources is paramount to work at the primary/secondary care interface. Nursing staff require an educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…This can be supported by findings from Hart et al (2005), who report on the importance of a mental health risk assessment framework specifically for use in EDs. According to Werrett et al (2001), an important issue in achieving good communication across the primary/secondary interface is effective and planned use of resources to ensure that timely, relevant high quality information is transmitted from one sector to another. In relation to the benefits of the care plan, it is significant that only 66% of respondents in this study agreed that the care plan assisted in the inter-hospital communication, while only 46% agreed that care plans assisted in communication between the ED and other acute or community hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…This can be supported by findings from Hart et al (2005), who report on the importance of a mental health risk assessment framework specifically for use in EDs. According to Werrett et al (2001), an important issue in achieving good communication across the primary/secondary interface is effective and planned use of resources to ensure that timely, relevant high quality information is transmitted from one sector to another. In relation to the benefits of the care plan, it is significant that only 66% of respondents in this study agreed that the care plan assisted in the inter-hospital communication, while only 46% agreed that care plans assisted in communication between the ED and other acute or community hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…These include failure to develop comprehensive discharge plans due to time and resource constraints, 43 44 failure to recognise the complexity of patients' needs, 45 poor communication within the multidisciplinary team in the acute hospital setting, 46 with patients and family members 47 48 and with clinicians in the community setting. 49 ICU survivors in our local qualitative research reported significant and unanticipated difficulties in their everyday lives following discharge home and were highly dependent upon close family members, often as a result of inadequate rehabilitative input, inadequate discharge planning, unrealistic expectations of recovery, ongoing morbidity and variability in access to community-based support. 30 Qualitative work among participants in a UK ICU follow-up service revealed that patients' psychosocial needs were rarely addressed during the acute hospital stay.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 97%
“…The focus groups were facilitated by AM using a semi-structured interview schedule which invited participants to share their experiences and views about patients information needs. Data from the telephone interviews and focus groups were analysed by content analysis [13] by two researchers (AM and JW) working independently before agreeing the final themes to emerge. Findings from the telephone interviews and the focus groups were triangulated to inform the development of a questionnaire used in Stage 2.…”
Section: Stagementioning
confidence: 99%